Effects of vitamin AD3E and C on immune responses of cattle to trivalent foot and mouth disease vaccine - Kizil, O.; Gul, Y. (Ecole Nationale Veterinaire Toulouse, 2008)
The aim of this study was to determine the effects of antioxidant vitamins on immune response of beef cattle to trivalent (type A, 0 and Asia 1) foot and mouth disease vaccine. A total of 48 healthy Brown Swiss cattle aged about one year old were used in this study. These animals were divided into four equal groups (A, B, C and D): Group A, received no vitamin; group B, received vitamin C; group C, received vitamins AD(3)E; and group D, received vitamins AD(3)E and vitamin C. Trivalent foot and mouth disease vaccines were administered in all groups. Blood samples were taken from the jugular vein of the animals on day 0 (the day of vaccination), 3, 14 and 21 of the experiment for the laboratory analysis. Antibody titers pre- and post-application period of trivalent foot and mouth disease vaccine were determined by ELISA. Serum vitamin A and beta-carotene, vitamin C and vitamin E levels were measured spectrophotometrically. Antibody response to the type A, 0 and Asia1 were not noticed in all groups on days 0 and 3, but was determined on days 14 and 21. The means of antibody titers for type A and Asia I were superior in group C and D. and the mean of antibody titer for type 0 is significantly higher in group D compared to those of the other groups. In conclusion, addition of vitamin AD(3)E plus vitamin C together with the injection of trivalent foot and mouth disease vaccine can be useful to provide more strength immunity probably by reducing negative effects caused by vaccination stress.
Keywords: Cattle; foot and mouth disease; vaccine; vitamin AD(3)E; vitamin C; immune response